Burnout Among the Urban and Rural Secondary School Teachers in Malaysia During the Movement Control Order - Roslan, Anis Nadihah; Roy, Atikah Afifah; Yee Von, Wong (Selangor Humaniora Review, 2022)
In the prolonged lockdown caused by the coronavirus epidemic, chronic exhaustion was seen in many academic workforces. This study aimed to evaluate and compare differences of burnout in the three components of emotional exhaustion, depersonalisation, and personal accomplishment—specifically, its relationship with the urban and rural areas of Malaysian secondary school teachers. The Maslach Burnout Inventory-Educators Survey received equal responses from sixty-two (62) teachers from Malaysia’s rural and urban locations (MBI-ES). The comparison data was evaluated using the t-test. Although secondary school teachers in urban parts of Malaysia were more likely to experience burnout than those in rural areas, the frequency of burnout among urban area teachers was comparable to that of teachers in rural Malaysia. The results also suggest that secondary school teachers’ demographic lockdown needs were not considered. Future research should identify the need for practical approaches to treating secondary school teacher burnout in urban and rural settings, respectively.